JOMEINO 2020
DOI: 10.31039/jomeino.2020.4.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Competitive intelligence and competitive advantage in pharmaceutical firms in developing economies: A review of Lagos State, Nigeria

Abstract: Competitive intelligence has remained a significant intervening variable on competitive advantage in the business world as part of survival and expansion. This reality exists in both the advanced and developing economies of the world. This study therefore examines the influence of competitive intelligence on competitive advantage of pharmaceutical firms in Lagos State, Nigeria. To achieve this objective, four hypotheses were formulated to establish whether a relationship existed between the two variables i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(1 reference statement)
1
7
0
Order By: Relevance
“…Similar conclusions were reported in the works of Qiu (2008) and Ezenwa et al (2018). Furthermore, the results of Nte et al(2020) study suggest that competitive intelligence methodology has a vast and beneficial outcome on the competitive advantage of firms. However, these results may not necessarily hold concerning the peculiarities of the Iraqi banking industry.…”
Section: Competitive Intelligence and Competitive Advantagesupporting
confidence: 88%
“…Similar conclusions were reported in the works of Qiu (2008) and Ezenwa et al (2018). Furthermore, the results of Nte et al(2020) study suggest that competitive intelligence methodology has a vast and beneficial outcome on the competitive advantage of firms. However, these results may not necessarily hold concerning the peculiarities of the Iraqi banking industry.…”
Section: Competitive Intelligence and Competitive Advantagesupporting
confidence: 88%
“…According to Uchegbulam et al (2015) competitive advantage gives a firm an edge over its rivals and ability to generate greater value for the firm and its stakeholders. Therefore, for a firm to ensure survival in such aggressive and turbulent competitive environment like Nigeria, SMEs must seek a better understanding and excellent knowledge of the environment and competitive forces which tend to reshape the behavioural patterns of the environment to gain competitive advantage and according to Nte et al (2020) those organization that can understand their environment, their competitors and establish competitive management strategies will win in this rapidly globalized information society.…”
Section: Competitive Advantage and Smesmentioning
confidence: 99%
“…Mamman (2020) investigated the effect of competitor orientation on innovation among SMEs in Yobe State, Nigeria, cross-sectional survey research design was adopted, the study found that competitor orientation significantly explains 11.7% of the total variance in innovation and was concluded that competitor orientation affects SMEs innovation, the study recommended as follows; that there is the need for SMEs managers and owners to employ better competitive method that give them upper hand above their competitors and the need for SMEs to maintain a constant relationship with their customers through business discussions forums, phone calls, email alerts of new products or services, after-service technical support and timely discount offers for key and specific customers who buy in bulk, and maintaining an active presence on social media among others. Nte et al (2020) conducted a study on competitive intelligence and competitive advantage in pharmaceutical firms in developing economics: A review of Lagos State, Nigeria. The study examines the influence of competitive intelligence on competitive advantage of pharmaceutical firms in Lagos State, Nigeria.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The research results showed the effect of CI on developing competitive advantage. Furthermore, Amiri et al (2017) A study by Nte et al (2020) discovered that CI could positively affect the organisation's growth, higher quality, and performance. While Agha, Atwa and Kiwan (2014) similarly in their study concluded that strategic intelligence positively impacts organisational performance.…”
Section: Competitive Intelligence and Sustainable Competitive Advantagementioning
confidence: 99%